Effect of plasma treatment on adhesion strength and moisture absorption characteristics between epoxy molding compound/silicon chip (EMC/chip) interface. (January 2019) - Oh, Gyung-Hwan; Joo, Sung-Jun; Jeong, Jae-Woo; Kim, Hak-Sung
Abstract: Reliability of interface between two dissimilar materials becomes an important issue due to increasing demands of high-density integrated circuits. Most of failures of semiconductor package occur at the interface between two dissimilar materials in high temperature reflow process, thus, adhesion strength under high temperature should be investigated. In this study, an adhesion shear test jig was newly devised to measure the adhesion strength of epoxy molding compound/Si chip (EMC/chip) interface at high temperature (200 °C). In order to investigate the effect of plasma treatment on adhesion strength and moisture absorption characteristics, the number of plasma treatments was varied. Also, moisture absorption time was varied to observe the moisture uptake and degradation of adhesion strength with respect to plasma treatment number. Atomic force microscope (AFM) was analyzed to verify the surface roughness of silicon chip, and scanning electron microscopy (SEM) was used to observe cross-sectional fractured morphology after adhesion strength test. From this study, it was found that the plasma treatments affect much the adhesion strength and moisture uptake at the interface between the EMC/Chip interface. Highlights: Measures the adhesion strength of the real semiconductor at high temperature. Stronger chemical bonding at the interface prevents the moisture absorption. Excessive plasma treatment degrades the adhesion strength by effective area reduction. Optimization of plasma treatment for enhancing the adhesion strength.